INOVASI PERAN PENGASUH PONDOK BAITU HUSODO DALAM PENANGGULANGAN PENYALAHGUNAAN NAPZA DI KOTA MOJOKERTO - Moch Solich (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2023)
Abstract. This research discusses the innovative role of caregivers in reducing cases of illegal drug abuse in Mojokerto City. Researchers conducted this research with the aim of reducing illegal drug abuse in the city of Mojokerto. This research has a case study design with qualitative methods. Content analysis includes: interview data, documents, and observation results. The results of research using the Bil Hikmah da'wah method, the role of caregivers for 60 participants with cases of illegal drug abuse who were successfully caught and sent to move back to the right path. The results of this caregiver innovation also include the establishment of Pondok Baitu Husodo and the Baitu Husodo Legal Aid Institute. This study makes a positive contribution in overcoming the problem of illegal drug abuse in Mojokerto City.